2015
DOI: 10.1542/peds.2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Exposure and Juvenile Idiopathic Arthritis: A Case–Control Study

Abstract: BACKGROUND AND OBJECTIVE: Recent evidence has linked childhood antibiotic use and microbiome disturbance to autoimmune conditions. This study tested the hypothesis that antibiotic exposure was associated with newly diagnosed juvenile idiopathic arthritis (JIA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 45 publications
(55 reference statements)
7
94
0
3
Order By: Relevance
“…Although some may argue that these unintended consequences are relatively infrequent, the risk of developing a complication from an untreated URI is even rarer. 11,12 Although the study conducted by Horton et al 9 does not confirm a causal relationship between antibiotic use and the development of JIA, it does raise further questions. Additional research is needed to fully elucidate the potential mechanisms that directly connect antibiotic use to the development of systemic inflammation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Although some may argue that these unintended consequences are relatively infrequent, the risk of developing a complication from an untreated URI is even rarer. 11,12 Although the study conducted by Horton et al 9 does not confirm a causal relationship between antibiotic use and the development of JIA, it does raise further questions. Additional research is needed to fully elucidate the potential mechanisms that directly connect antibiotic use to the development of systemic inflammation.…”
mentioning
confidence: 94%
“…4 Because antibiotic exposure results in significant intestinal dysbiosis, 5 the relationship between antibiotic use and the development of chronic diseases has been investigated, with some convincing evidence directly associating antibiotic exposure with obesity and inflammatory bowel disease. [6][7][8] In this issue of Pediatrics, Horton et al 9 evaluated the association between antibiotic exposure and a new diagnosis of juvenile idiopathic arthritis (JIA) in children aged 1 to 15 years. The authors performed a nested case-control study by using a UK population-representative medical records database.…”
mentioning
confidence: 99%
“…15 Nested case-control designs efficiently produce unbiased estimates of incidence rate ratios. 21 THIN contains anonymized patient data on demographics, diagnoses, referrals, and outpatient prescriptions by general practitioners (GPs) collected during routine primary care.…”
Section: Methodsmentioning
confidence: 99%
“…Among drugs linked to psoriasis are antibiotics, including tetracyclines, mostly on the basis of older case reports and one survey-based study that lacked rigorous methods. 1012 More recent studies 1315 have found an association between childhood antibiotic use and 2 related pediatric autoimmune diseases: inflammatory bowel disease (IBD) and juvenile idiopathic arthritis (JIA). Antibiotics disrupt human microbiota, and microbial disturbance has been implicated in the pathogenesis of pediatric IBD and JIA.…”
mentioning
confidence: 99%
“…Vedno, ko predpišemo antibiotik, je potrebno pomisliti tudi na morebitne dolgoročne neželene učinke antibiotikov. V zadnjem času je bilo objavljenih več raziskav, ki dokazujejo povezavo med uporabo antibiotikov v zgodnjem otroštvu in različ-nimi avtoimunimi boleznimi (juvenilni revmatoidni artritis, kronična vnetna črevesna bolezen) ter debelostjo, kar lahko predstavlja le vrh ledene gore vseh dolgoročnih neželenih učinkov (30)(31)(32)(33). Selekcijski pritisk antibiotikov na normalno floro in patogene bakterije in po izločanju v okolje je dobro znan, vendar se premalo upošteva pri predpisovanju.…”
Section: Izvirni Znanstveni čLanekunclassified